SEJARAH LINGKUNGAN SEBAGAI PENDIDIKAN PENGURANGAN RESIKO BENCANA DI KABUPATEN KETAPANG KALIMANTAN BARAT - Basuki Wibowo; Agus Dediansyah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTThe learning of environmental history developed in Ketapang District can be utilizedas an education for natural disaster risk reduction. This study aims to determine andexplore the history of the environment and the potential contained in oral history to bemade as a disaster risk reduction education in Ketapang Regency, West Kalimantan.This study uses qualitative research methods with a form of embedded case studystrategies. Data sources used are informants, places and events, and documents. Datacollection techniques using direct observation techniques, in-depth interviews, anddocument studies. The sampling technique used is purposive sampling. Data validityuses triangulation and data analysis techniques use interactive analysis techniques. ThePotential of Environmental History as Disaster Risk Reduction Education (PPRB) inKetapang Regency, West Kalimantan is very large. Utilization of history known to thecommunity from its environment will form its own memory. Disaster Risk ReductionEducation (PPRB) is oriented to the development of a community and is active, creative,innovative, effective. Through learning the history of the environment will form thecharacter of people who have environmental concerns so that the risk of naturaldisasters due to environmental damage can be overcome and minimized.Keywords: Environmental history, Disaster Risk Reduction